QLIF-09. LONGTERM SURVIVAL IN GLIOBLASTOMA PATIENTS AFTER TUMOR TREATING FIELDS (TTFIELDS) THERAPY - Rulseh, Aaron (Neuro Oncol, 2017)
INTRODUCTION: Glioblastoma (GBM) is the most common and malignant primary intracranial tumor and traditionally has a median survival of only 10 to 14 months, with only 3 to 5% of patients surviving more than three years. Recurrence (RGBM) is nearly universal, and further decreases the median survival to only 5 to 7 months with optimal therapy. METHODS: Tumor treating fields (TTFields; Optune™) therapy is a novel treatment technique that has recently shown significant prolonged progression free survival and overall survival in newly diagnosed GBM. This therapy is approved for the treatment of newly diagnosed and recurrent GBM and is based on the principle that low intensity, intermediate frequency alternating electric fields (100 to 300 kHz) have an anti-mitotic effect in specific cell types. The applied fields disrupt the mitotic spindle, microtubule assembly and the segregation of intracellular organelles during cell division, leading to apoptosis or mitotic arrest. RESULTS: Our center was the first in the world to apply TTFields treatment to histologically proven GBM in a small pilot study of 20 individuals (10 GBM and 10 RGBM) in 2004 and 2005, and 4 of the original 20 patients are still alive today (2 GBM, 2 RGBM), in good health and no longer receiving any treatment roughly 12 years after initiating TTFields therapy, with no clinical or radiological evidence of recurrence. Two of the 4 surviving patients exhibited radiological signs of tumor growth initially, before the tumor regressed in size after a median of 4 months of continuous treatment. CONCLUSION: Our results indicate that TTFields treatment may be remarkably successful for both newly diagnosed and recurrent GBM patients. We recommend that TTFields treatment should be applied for a sufficient amount of time, and that initial radiologic progression following treatment initiation should not be considered a reason to discontinue treatment.